Lung ultrasound in diagnosing neonatal respiratory distress syndrome: a meta-analysis - Hanum Ferdian; Dian Ibnu Wahid; Samad Samad; Anggun Esti Wardani; Guntur Surya Alam; Annang Giri Moelyo (Indonesian Pediatric Society, 2019)
Background Neonatal respiratory distress syndrome (NRDS) is commonly diagnosed by clinical sign and symptoms, blood gas analysis, and chest x-ray. In the past, lung ultrasound (LUS) was not standard for NRDS examination. Many studies show that ultrasound diagnostic tool for NRDS is accurate, reliable, low cost, easy to use, and safe because due to no ionizing radiation. Objective To determine the sensitivity and specificity of LUS in diagnosing NRDS. Methods This meta-analysis study was conducted LUS as a diagnostic tool for NRDS. Inclusion criteria were all studies from PubMed, Embase, and The Cochrane Library, without any limitation on published journals, as well as using keywords or search terms of ultrasound, neonatal, and respiratory distress syndrome. Statistical analysis was undertaken using MedCalcÂ® version 18.2 software. Results Seven studies with a total of 580 patients met the inclusion criteria. Proportional meta-analysis obtained random effects models, with total sensitivity of LUS was 97.2% (95% CI for I2 74.24 to 92.88; P<0.0001) and specificity of LUS was 94.8% (95% CI for I2 88.60 to 98.03; P<0.00001). Conclusion Lung ultrasound should be considered as a diagnostic tool for NRDS because it is high in sensitivity and specificity, inexpensive, safe, as well as limited radiation exposure.